Typification of names of taxa belonging to Festuca arundinacea (≡Schedonorus arundinaceus) aggregate (Poaceae) in Hackel’s herbarium (W) - Ardenghi, Nicola M.g.; Signorini, Maria Adele; Parolo, Gilberto; Rossi, Graziano; Pignotti, Lia; Vitek, Ernst; Foggi, Bruno (Phytotaxa, 2013)
This paper selects lectotypes for several names proposed by Hackel and Wiesbaur belonging to Schedonorus aggr. "arundinaceus": Festuca elatior subvar. conferta, F. elatior subvar. orientalis Hack., F. elatior subvar. strictior, F. elatior subvar. subalpina, and F. uechtritziana. The holotype of F. elatior subvar. longiglumis and F. elatior subvar. spuria are here established. All types are conserved at W and BRNU. Links to type scans are provided.